Prevalence and Antimicrobial Susceptibility of Staphylococcus aureus at the Kenyatta National Hospital, Nairobi (The East and Central African Journal of Pharmaceutical Sciences, 2018)
A cross sectional study of 115 patients admitted at the Department of Orthopedics, Kenyatta Hospital, Nairobi, Kenya was carried out to determine the prevalence and antibiotic susceptibility of Staphylococcus aureus isolated from infected wounds. The prevalence of Staphylococcus aureus was 33.0 %. The drugs tested and their corresponding sensitivity were amoxycillin (13.2 %), co-amoxiclav (39.5 %), oxacillin (55.3 %), erythromycin (44.7 %), gentamicin (60.5 %), ciprofloxacin (62.2 %) minocycline (86.8 %), cefuroxime (57.9 %) and clindamycin (84.2 %). These results show the sensitivity profile of Staphylococcus aureus and can be used to choose suitable drugs in the management of wounds for hospitalized patients.
Keywords: Prevalence; antimicrobial susceptibility; Staphylococcus aureus